THE EFFECT OF HEDONIC SHOPPING MOTIVATION, SHOPPING LIFESTYLE AND FEAR OF MISSING OUT ON IMPULSIVE BUYING WITH POSITIVE EMOTION AS A MEDIATION IN GENERATION Z (SHOPEE E-COMMERCE USER CASE STUDY) - Reni Pratiwi Sihombing; Rd. Nurafni Rubiyanti; Mahir Pradana (PT. Jurnal Center Indonesia Publisher, 2025)
Shopee, as one of the e-commerce establishments established in 2015 and part of the Sea Group in Southeast Asia, has succeeded in creating a safe, user-friendly and fast online shopping platform. With strong operations in seven markets in Southeast Asia, Shopee not only provides a platform for buyers to find products, but also provides training and support to their sellers. The rapid growth of e-commerce in Indonesia is also influenced by factors such as the increase in population, increasing smartphone and internet users, and the development of financial technology companies. The convenience of online shopping encourages consumers to buy various desired products so that they are encouraged to behave consumptively. This then stimulates the phenomenon of impulse buying in consumers. Currently, economic activities are dominated by Generation Z's behavior to carry out activities such as scrolling, online shopping, and making transactions. Some marketplaces have not paid attention to the positive emotions of consumers with the Generation Z group in the target market, hedonic shopping motivation, fear of missing out, and shopping lifestyle that can trigger impulsive purchases which are part of the consideration of the preparation and strategy of innovative marketing targets according to the needs of market psychology. This study aims to find out how much respondents assess hedonic shopping motivation, fear of missing out, and shopping lifestyle, find out the influence of hedonic shopping motivation, fear of missing out, and shopping lifestyle on impulse buying generation Z, find out the influence of positive emotions on impulse buying generation Z, to know the influence of hedonic shopping motivation, fear of missing out and shopping lifestyle on impulse buying through positive emotions. This study uses a quantitative method. The sampling technique uses purposive sampling. The data obtained was 385 respondents by distributing questionnaires online. The respondents in this study are Generation Z Shopee users in Indonesia. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) which was then processed with SMARTPLS. The results of this study are hedonic shopping motivation, fear of missing out, shopping lifestyle, positive emotion have a significant positive effect on impulse buying.